The effect of working conditions and coworking on employee job satisfaction - Nurvitasari, Farida (Faculty of Economics and Business Mulawarman University, 2019)
This research aimed to examine the effect of working conditions and coworking on employee job satisfaction. This research belonged to quantitative research. The analysis technique used was multiple linear regression analysis. The data collection technique was done by distributing the questionnaires to 90 respondents, then it was processed by using SPSS. The results showed that working conditions and coworking had a significant effect on employee job satisfaction.